Comprehensive evaluation of root and root canal morphology of mandibular second molars in a Saudi subpopulation evaluated by cone-beam computed tomography - Moazzy I. Almansour; Saad M. Al‑Zubaidi; Abdulmjeed S. Enizy; Ahmed A. Madfa (BMC Oral Health, 2022)
Abstract Background The study's goal was to use Cone Beam Computed Tomography (CBCT) to assess the root and root canal anatomy of mandibular second molars with C-shaped root canal configurations in residents of the Hail district. The impact of gender and side on the frequency of root canal morphology was considered. Methods The sample size for this study was 304 untreated mandibular second molars with completely developed roots on the right and left sides. Using CBCT on the teeth, the root form and canal morphology for each root are based on Vertucci's classification. The occurrence of canals in the shape of a C. The prevalence and resemblance of the left and right sides or men and females were investigated. The Chi-square test was performed to evaluate the findings. Results Of the 304 mandibular second molars studied, 286 teeth had two roots (94.1%), whilst 13 (4.3%) were C-shaped root canal systems. 77 molars (25.3%) had two canal orifices, 219 (72.0%) had three canal orifices, and six (2.0%) and one (0.3%) had four and five root canal orifices, respectively. Type IV was the most common for mesial root, accounting for 57.7% of the sample (n = 176). For distal root, the most common occurrence was type I, which occurred 282 times (96.60%). The most prevalent root canal morphology was the presence of two canals in the mesial root and one canal in the distal root of teeth with two distinct roots (variant 3). (69.4%). The overall prevalence of C-shaped root canal systems is (4.3%) (n = 13). Conclusions The patient's race is an undeniable factor that influences root canal anatomy. The root canal morphology of mandibular second molars revealed significant differences between Saudi subpopulations. The majority of mandibular second molars had two roots and three root canals. When treating these molars, the presence of a C-shaped root canal system must be taken into account.